A novel rhodamine-3, 4-dihydro-2H-1, 3-benzoxazine conjugate as a highly sensitive and selective chemosensor for Fe3+ ions with cytoplasmic cell imaging possibilities1. Issue 12 (21st June 2015) - Molla, Habib Ali; Bhowmick, Rahul; Katarkar, Atul; Chaudhuri, Keya; Gangopadhyay, Sumana; Ali, Mahammad
<x xml:space="preserve">Abstract</x> A novel rhodamine-3, 4-dihydro-2H-1, 3-benzoxazine conjugate exhibits excellent selectivity towards Fe3+ both in extra and intracellular conditions.